The hierarchical recourse to the congregation of Roman Curia - Leszczyński, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The Code of Canon Law of 1983 referring to hierarchical recourse, does not limit it merely to the appeal to the Congregation of Roman Curia, but it refers to each recourse sought in a higher executive administration organ. The subject of interest of the author is the hierarchical recourse sought in the Roman Curia after exhausting the hierarchical path of lower grades. According to can. 1737 § 1 of the Code of Canon Law, anyone who considers himself injured with the decree can seek recourse to the hierarchic superior of the one who delivered the decree. Therefore the author is speaking about the subject of the recourse, the motive as well as the procedure to be undertaken in order to obtain the desired goal, appeal or change of the harmful act.